Piạ Susa: Death Rituals in the Islam Masade Community in Sangihe, North Sulawesi - Macpal, Sunandar; Fata, Ahmad Khoirul; Hamani, Sintia; Hubu, Awaludin (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This article discusses the death traditions in the Islam Masade community in Sangihe, North Sulawesi, known as Piạ Susa. The study is based on the hybrid and syncretic religious practices of the community. The blending of Islamic elements, local beliefs, and Christianity has shaped the religious beliefs and traditions of Islam Masade into something unique and distinctive, including the Piạ Susa tradition. This research uses an ethnographic method to provide a clear depiction of the Piạ Susa tradition. The researchers engaged directly with the Islam Masade followers in Sangihe and relied on key figures within the community as research subjects. The study reveals that the Piạ Susa tradition is significantly influenced by Islamic teachings, mixed with various local elements, resulting in a hybrid tradition. From death announcements, funerals, prayers, to post-burial rituals, Islamic practices are infused with local nuances. In this perspective, Islam Masade can be seen as a localized expression of Islam in Sangihe or as a form of cultural dissemination from pure Islam. Besides serving as a tribute to the deceased, Piạ Susa also represents a sacred “life transition” process. Piạ Susa further serves as a means for the Islam Masade community to strengthen social solidarity, affirm identity, and maintain the existence of Islam Masade amidst dominant cultural influences.